Non-performing loans and productivity in Chinese banks: 1997 - 2006 - Kent Matthews; Jianguang Guo; Nina Zhang (Cardiff University, Cardiff Business School, 2007)
This study examines the productivity growth of the nationwide banks of China over the ten years to 2006. Using a bootstrap method for the Malmquist index estimates of productivity growth are constructed with appropriate confidence intervals. The paper adjusts for the quality of the output by accounting for the non-performing loans on the balance sheets and test for the robustness of the results by examining alternative sets of outputs. The productivity growth of the state-owned banks is compared with the Joint-stock banks and it determinants evaluated. The paper finds that average productivity of the Chinese banks improved modestly over this period. Adjusting for the quality of loans, by treating NPLs as an undesirable output, the average productivity growth of the state-owned banks was zero or negative while productivity of the Joint-Stock banks was markedly higher.
Keywords: D24; G21; 330; Bank Efficiency; Productivity; Malmquist index; Bootstrapping; Bank; Produktivität; Bootstrap-Verfahren; China